CFD Simulation of Engine Room Ventilation Systems: A Case Study of TB Hasnur 08 Tugboat Main Engine - Rhomadon Hady Siswanto; Agoes Agoes; Sutopo Puewono Fitri (International Journal of Marine Engineering Innovation and Research, 2026)
Excessive heat in the engine room of the tugboat TB Hasnur 08 represents a critical operational issue, as it directly affects operator comfort, main engine combustion efficiency, and the overall reliability of onboard machinery systems. This study aims to design, evaluate, and validate an optimal engine room ventilation model using a Computational Fluid Dynamics (CFD) approach. The analysis focuses on identifying heat pocket locations, evaluating various airflow arrangements, and formulating data-driven ventilation design guidelines. The calculation of air supply requirements and heat evacuation is conducted in accordance with ISO 8861:1998, which serves as the primary reference standard. The research methodology consists of an empirical study followed by CFD simulations. The simulations examine variations in air velocity and airflow configuration through the application of exhaust systems, resulting in five ventilation configurations, referred to as Variation 0 to Variation 4. Under existing conditions (Variation 0), the engine room air temperature ranges from 45.05°C to 46.05°C. Variation 1 reduces the temperature to 42.85°C–43.95°C, while Variation 2 achieves 42.85°C–42.95°C. Variation 3 applies air velocity in compliance with ISO 8861, resulting in a further reduction to approximately 41.85°C–42.95°C. Variation 4 utilizes the same air velocity as Variation 3 with an additional exhaust duct at Frame 16/17, producing temperatures of 42.85°C–43.25°C. The results indicate that Variation 3 provides the most effective temperature reduction. Furthermore, CFD analysis demonstrates strong capability in predicting thermal behavior resulting from changes in air velocity, duct dimensions, and ventilation configurations.